The Role of the Palestine Red Crescent Society in Promoting the Convention on the Prevention of the Crime of Genocide: The Baptist Hospital Massacre in the Gaza Strip - a Model: the international and political journal - Abdel Nafeh , Assistant Prof. Dr. Mohamed; Fadel, Prof. Dr. Shaima Adel (The International and Political Journal, 2024)
Anything that goes beyond merely harming a person's life, health and dignity and extends to other dimensions and goals, such as the total or partial elimination of national, ethnic, racial or religious groups, is considered a crime of genocide, while addressing the elements of such crimes materially, morally and internationally. Accordingly, a number of international non-governmental organizations and associations have emerged with an interest in such crimes, providing humanitarian assistance. Given the circumstantial and temporary nature of a large number of these international non-governmental organizations distributed throughout the world, their work constituted an important milestone. The researchers decided to shed light on such effective organizations and associations. An applied model was adopted for the work of such organizations and a statement of their work to reduce genocide crimes. The Palestinian Red Crescent Society and its humanitarian role towards the Baptist Hospital massacre in 2023 were highlighted.